Hubungan Asupan Kalsium, Magnesium dan Zat Besi dengan Kejadian Dismenore Primer pada Siswi di SMK Muhammadiyah Bumiayu - Maula, Athiyatul, Tri Wibowo Anang S.B., S.KM, M.Gizi (2017)
Background: Primary dysmenorrhea is abdominal pain experienced by some of childbearing age women at the beginning of menstruation. In Indonesia, the incidence of dysmenorrhea ranges between 45-95% among women of the fertile age. Suspected factors causing dysmenorrhea include psychiatric, constitutional (anemia, chronic disease), endocrine, and allergies. Some nutrients also linked to the incidence of dysmenorrhea such as calcium, magnesium, and iron. Objective: This study aimed to determine the correlation between calcium, magnesium, iron intakes and the incidence of primary dysmenorrhea on female students at Muhammadiyah Bumiayu Vocational High School. Methods: The study was observational with cross sectional approach. The sampling technique using simple random sampling with total 64 samples. Dysmenorrhea incidence data were obtained using the Universal Pain Assessment Tool. Calcium, magnesium and iron intakes were obtained using a semi-quantitative Food Frequency Questionnaire (FFQ). Data analysis using Fisher's Exact test. Results: A total of 89% of the sample experienced primary dysmenorrhea. Samples with less calcium intake were 84%, the samples with more magnesium intake were 75% and the samples with less iron intake were 91%. Statistical analysis showed the value of p = 0.001 (calcium), p = 0.178 (magnesium), and p = 0.014 (iron). Conclusion: There was a correlation between calcium and iron intakes and the incidence of dysmenorrhea. There was no correlation between magnesium intake and the incidence of dysmenorrhea. Keywords : Calcium intake, dysmenorrhea, magnesium intake, iron intake Library : 46 (1978-2015)